2014
DOI: 10.1007/s40618-014-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25 hydroxyvitamin D in employees of a Middle Eastern university hospital

Abstract: Vitamin D deficiency is common among hospital workers. This finding reinforces the need for vitamin D supplementation in these high-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
4
11
1
Order By: Relevance
“…Furthermore, our results indicated that patients with schizophrenia, as well as the healthy ones, had a vitamin D deficiency, similar to previous studies [2,4,36,37,40,41]. Other studies conducted in Lebanon had shown a hypovitaminosis D in the healthy population [35,[42][43][44][45].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our results indicated that patients with schizophrenia, as well as the healthy ones, had a vitamin D deficiency, similar to previous studies [2,4,36,37,40,41]. Other studies conducted in Lebanon had shown a hypovitaminosis D in the healthy population [35,[42][43][44][45].…”
Section: Discussionsupporting
confidence: 91%
“…Our sample mean serum 25(OH)D level (28.15±13.93 ng/ml) was higher and prevalence rate of vitamin D deficiency (≤ 20 ng/ml) (32%) were lower than those reported in two studies involving samples of healthy Lebanese adults (Gannagé-Yared et al, 2014;Malaeb, Hallit, & Salameh, 2017); this could be attributed to differences in characteristics among study samples. Mean serum 25(OH)D level was found to be 15.61 ± 7.91 ng/ml and prevalence rate of vitamin D deficiency (< 20 ng/ml) was reported at 71.4% among a sample of 392 healthy private hospital employees (nurses, medical assistants, technicians, secretaries, medical engineers, administrative employees, etc., excluding doctors and medical students) aged 20-63 years (mean age= 41.02 ±11.3 years) (81% women); none of them had been taking vitamin D supplement.…”
Section: Discussioncontrasting
confidence: 87%
“…Mean serum 25(OH)D level was found to be 15.61 ± 7.91 ng/ml and prevalence rate of vitamin D deficiency (< 20 ng/ml) was reported at 71.4% among a sample of 392 healthy private hospital employees (nurses, medical assistants, technicians, secretaries, medical engineers, administrative employees, etc., excluding doctors and medical students) aged 20-63 years (mean age= 41.02 ±11.3 years) (81% women); none of them had been taking vitamin D supplement. Similar to our findings, there was no significant associations between serum 25(OH)D levels and age, sex, BMI, and sunscreen use; however, contrary to our study, serum 25(OH)D levels showed significant associations with educational level, and weekly hours of sun exposure (Gannagé-Yared et al, 2014). The two other studies looked at serum 25(OH)D levels and their determinants in samples of university students.…”
Section: Discussionsupporting
confidence: 70%
“…In Lebanon, Gannage-Yared et al studied 318 female hospital workers with a mean age of 40.4 ± 11 years and reported vitamin D deficiency (serum 25(OH)D < 23.5 nmol/L) in 25% and insufficiency (serum 25(OH)D 23.75–53.75 nmol/L) in 50% of women, with no significant correlations with BMI or age [34]. …”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Data on micronutrient deficiencies in men residing in the Middle East appears limited and mainly focuses on vitamin D, with the highest deficiency and insufficiency levels reported in Lebanon at 27% and 54%, respectively [34], as well as in the UAE and KSA at ~40% [11,28,38]. …”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%